Comprenhensive reparation as a prevailing principle in the responsability of the state –a perspective based on the constitutional court and the Colombian council of state case-law- [La reparación integral como principio prevalente en la responsabilidad del estado –una visión a partir de la jurisprudencia de la corte constitucional y del consejo de estado Colombiano–] (2020)
This paper addresses comprehensive reparation as a fundamental right and guiding principle in civil and State liability so that it is taken into account in a prevalent manner when assessing material and immaterial damages suffered by people. Due to the need to weigh such principle, there are many discussions raised from a normative, doctrinal, and – even-jurisprudential point of view, not only in the domestic sphere but also in the international sphere. However, its evolution has been remarkable and, currently, judges must apply it based on grounds of protection of human rights and international humanitarian law. For this research, the development, the analysis, the content, and the scope of the reparation principle was studied in the various international human rights instruments. Afterward, the research focuses on the criteria used by the Constitutional Court and the Council of State from 1991 onwards; along with the relevant doctrine on this subject. Lastly, the paper argues that the comprehensive reparation principle has consolidated as a prevalent principle within Colombian case-law which faces interesting interaction with the block of constitutionality and conventionality in the search of true restorative and transformative justice. © 2020, Corporacion Universitaria Republicana. All rights reserved.